Elaboración de un manual de procesos interactivos a partir de la identificación, análisis y evaluación de la seguridad y riesgos eléctricos en la instalación y operación de transformadores de distribución. - Abril Garcés, Ernesto Manuel (2013)
This research work has carried out Safety studies in the installation and operation of distribution transformers, which influence electrical risk, determining the safety conditions to which workers are subjected in the installation of distribution transformers, through measurements of safety distances and proximity to energized lines to avoid electrocution; then the contacts of people or animals with electrical live points were characterized, by means of resistance measurements of: ground (RS) to verify with the standard of the EEASA design guide, using the MEGER grounding equipment.